Synthesis and photoluminescence of Mn4+ in M4Al14O25 (M = Sr or Mg) compounds as red-light phosphors for white LED. (September 2019) - Xiong, F.B.; Lin, L.X.; Lin, H.F.; Meng, X.G.; Lian, S.Y.; Zhu, W.Z.
Highlights: Deep red-light-emitting phosphor Mn 4+ -doped M4 Al14 O25 (M = Sr or Mg) have been obtained via solid-state reaction. Structure, luminescent properties of those phosphors are well studied and characterized. The CIE coordinates ( X, Y ) of 0.5 at.% Mn 4+ -doped Mg4 Al14 O25 are (0.631, 0.252). Thermal stability of Mn 4+ -doped Mg4 Al14 O25 need be further improved. Abstract: Red-light-emitting phosphors Mn 4+ -doped M4 Al14 O25 (M = Sr or Mg) were synthesized by solid-state reaction at 1400 °C in air, and their luminescent properties were initially investigated for their applications in warm white-light-diodes (W-LEDs). The excitation spectra of Mn 4+ -doped M4 Al14 O25 (M = Sr or Mg) showed that those phosphors were efficiently excited by near ultraviolet (UV) or blue LED chips, and those phosphors exhibited deep red emission band around 650 nm arising from the spin-forbidden 2 E → 4 A 2 transition of Mn 4+ . The energy transfer mechanism in Mn 4+ -doped Mg4 Al14 O25 phosphor was found to be the electric dipole-dipole interaction and the critical distance of energy transfer between the Mn 4+ ions was obtained to be about 1.384 nm. The Commission International de L'Eclairage (CIE) chromaticity coordinates of 0.5at.% Mn 4+ -doped Mg4 Al14 O25 were (0.631, 0.252). The temperature-dependent luminescence indicated Mn 4+ -doped M4 Al14 O25 phosphor was poor thermal-stable. Further work related to improve its thermal stability need be executed for Mn 4+ -doped M4 Al14 O25 (M = Sr or Mg) as a promising candidate of red-component for warm W-LEDs.